2023
DOI: 10.3390/brainsci13081146
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Probable REM Sleep Behavior Disorder in Parkinson’s Disease

Santiago Perez-Lloret,
Guenson Chevalier,
Sofia Bordet
et al.

Abstract: Patients with Parkinson’s Disease (PD) experience REM sleep behavior disorder (RBD) more frequently than healthy controls. RBD is associated with torpid disease evolution. To test the hypothesis that differential genetic signatures might contribute to the torpid disease evolution in PD patients with RBD we compared the rate of genetic mutations in PD patients with or without probable RBD. Patients with a clinical diagnosis of PD in the Parkinson’s Progression Markers Initiative (PPMI) database entered the stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Moreover, in a recent study Perez-Lloret et al found that GBA _N370S_rs76763715 was associated with more frequent pRBD among PD patients. In addition, some GBA variants, like rs2230288/E326K, rs75548401/T369M, and rs369068553/V460L, were also associated with more frequent non-motor symptoms, including RBD, as well as with a more aggressive motor disease [ 13 ].…”
Section: Genes Involved In Pd Patients’ Sleep Disordersmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, in a recent study Perez-Lloret et al found that GBA _N370S_rs76763715 was associated with more frequent pRBD among PD patients. In addition, some GBA variants, like rs2230288/E326K, rs75548401/T369M, and rs369068553/V460L, were also associated with more frequent non-motor symptoms, including RBD, as well as with a more aggressive motor disease [ 13 ].…”
Section: Genes Involved In Pd Patients’ Sleep Disordersmentioning
confidence: 99%
“…The zinc finger protein 184 ( ZNF184 ) is located on chromosome 6 and encodes a Kruppel C2H2-type zinc-finger protein family member, which participates in gene expression regulation [ 57 ]. The genetic basis of pRBD in PD was recently examined and the ZNF184 _rs9468199 polymorphism was found to increase the risk of pRBD [ 13 ]. This variant was previously associated with more frequent RBD in the Chinese population [ 58 ].…”
Section: Genes Involved In Pd Patients’ Sleep Disordersmentioning
confidence: 99%
See 3 more Smart Citations